Cardioautonomic lability assessed by heart rate variability changes in Royal Canadian Mounted Police cadets during the cadet training program - Teckchandani, Taylor A.; Neary, J. Patrick; Andrews, Katie L.; Maguire, Kirby Q.; Jamshidi, Laleh; Nisbet, Jolan; Shields, Robyn E.; Afifi, Tracie O.; Sauer-Zavala, Shannon; Lix, Lisa M.; Krakauer, Rachel L.; Asmundson, Gordon J. G.; et al. (Frontiers in Psychology, 2023)
Objective: The current study examined variations in cardioautonomic lability during the Royal Canadian Mounted Police (RCMP) Cadet Training Program (CTP) between cadets starting their training who did or did not screened positive for one or more mental health disorders (i.e., posttraumatic stress disorder [PTSD], major depressive disorder [MDD], social anxiety disorder [SAD], generalized anxiety disorder [GAD], panic disorder [PD], alcohol use disorder [AUD]). Methods: Electrocardiogram (ECG) signals integrated into Hexoskin garments were used to record ECG and heart rate Over the 26-week CTP. There were 31 heart rate variability (HRV) parameters calculated using Kubios Premium HRV analysis software. Mann-Whitney U-tests were used to perform groupwise comparisons of participant raw values and HRV during the CTP.Results: A total of 157 cadets (79% male) were screened for any mental disorder using selfreport surveys and then grouped by positive and negative screening. Analyses indicated a statistically significant (p < .05) decrease in low frequency (LF): High Frequency (HF) variability during CTP, but only for cadets who screened positiveendorsed clinically significant anxiety symptoms on the GAD-7 at the start of their training. There were no other statistically significant groupwise differences.The results indicate the participants have excellent cardiac health overall and suggest potentially important differences between groups, such that cadets who endorsed clinically significant anxiety symptoms on the GAD-7screened positive for GAD showed less variability in the LF:HF ratio over the course of the CTP. The relatively lower variability suggests decreased parasympathetic tone in those without clinically significant anxiety symptoms. The results also have important implications for future investigations of cardioautonomic dysfunction and chronic hypothalamic pituitary adrenal (HPA) axis deviations in policing populations with anxiety disorders; specifically, cardioautonomic inflexibility related to cardiovascular morbidity and mortality. In any case, the current results provide an important baseline for future cardiac research with cadets and serving officers.